2011
DOI: 10.1200/jco.2011.36.2236
|View full text |Cite
|
Sign up to set email alerts
|

Bevacizumab in Combination With Chemotherapy As First-Line Therapy in Advanced Gastric Cancer: A Randomized, Double-Blind, Placebo-Controlled Phase III Study

Abstract: Although AVAGAST did not reach its primary objective, adding bevacizumab to chemotherapy was associated with significant increases in progression-free survival and overall response rate in the first-line treatment of advanced gastric cancer.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

15
718
3
5

Year Published

2013
2013
2021
2021

Publication Types

Select...
9

Relationship

3
6

Authors

Journals

citations
Cited by 1,006 publications
(741 citation statements)
references
References 31 publications
15
718
3
5
Order By: Relevance
“…No prospective trial investigating systemic chemotherapy specified in hepatic metastases has been reported, with the exception of one small pilot study involving 8 patients [29]. In recent phase III trials of first-line chemotherapy against advanced/metastatic gastric cancer, median survival time ranged from 11 to 15 months [30][31][32][33][34]; 5-year survivors were rarely observed. In a report that integrated 643 patients enrolled in five separate prospective trials performed by the Japan Clinical Oncology Group, the 5-year survival rate of patients with metastasis confined to the liver and treated with systemic chemotherapy alone was 1.7 % [35].…”
Section: Resultsmentioning
confidence: 99%
“…No prospective trial investigating systemic chemotherapy specified in hepatic metastases has been reported, with the exception of one small pilot study involving 8 patients [29]. In recent phase III trials of first-line chemotherapy against advanced/metastatic gastric cancer, median survival time ranged from 11 to 15 months [30][31][32][33][34]; 5-year survivors were rarely observed. In a report that integrated 643 patients enrolled in five separate prospective trials performed by the Japan Clinical Oncology Group, the 5-year survival rate of patients with metastasis confined to the liver and treated with systemic chemotherapy alone was 1.7 % [35].…”
Section: Resultsmentioning
confidence: 99%
“…The antitumor activity observed was significant with a RR of 17.9% and a median OS of 6.3 months. However, in this setting, other recently evaluated combinations including those employing combinations of capecitabine with either oxaliplatin or cisplatin combinations have demonstrated improved clinical activity (5).…”
Section: Discussionmentioning
confidence: 99%
“…For patients demonstrating HER2 overexpression or amplification, trastuzumab combined with systemic therapy has become the standard treatment (4). Combination regimens have been shown to increase efficacy with response rates (RR) ranging from 30% to 50%, progression-free survival (PFS) of 3-7 months and OS of up to 11 months, but not without significantly increasing treatment-related toxicity (4)(5)(6)(7)(8). Given the high percentage of patients who fail to respond to current therapies there is a critical need for novel, effective, and personalized therapeutic strategies for the treatment for gastric cancer.…”
Section: Introductionmentioning
confidence: 99%
“…Germline DNA was available from white patients treated in six placebo-controlled phase III clinical trials: (1) NO16966 (ClinicalTrials.gov identifier NCT00069095), which tested capecitabine-oxaliplatin versus 5-fluorouracil/folinic acid-oxaliplatin with or without bevacizumab as first-line treatment for mCRC [3]; (2) AViTA (ClinicalTrials.gov identifier NCT01214720), which tested the addition of bevacizumab to gemcitabine and erlotinib as first-line treatment for metastatic pancreatic cancer [29]; (3) AVAiL (ClinicalTrials.gov identifier NCT00806923), which tested the addition of bevacizumab to standard firstline chemotherapy (cisplatin-gemcitabine) for advanced/ recurrent non-squamous NSCLC [30,31]; (4) AVOREN (ClinicalTrials.gov identifier NCT00738530), which tested the addition of bevacizumab to interferon a-2a as first-line treatment for metastatic clear-cell RCC [6,32]; (5) AVADO (ClinicalTrials.gov identifier NCT00333775), which tested the addition of bevacizumab to docetaxel as first-line treatment for metastatic human epidermal growth factor receptor 2-negative breast cancer [33]; and (6) AVAGAST (ClinicalTrials.gov identifier NCT00548548), which tested the addition of bevacizumab to capecitabinecisplatin chemotherapy as first-line treatment for advanced gastric cancer [34].…”
Section: Methodsmentioning
confidence: 99%